Comparing The Effectiveness of Mindfulness-Based Therapy and Paradoxical Treatment on Distress Tolerance in Adolescents with Social Anxiety Symptoms - Noorollahi, Atefeh; Shahabizadeh, Fatemeh; Nasri, Maryam (International Journal of Education and Cognitive Sciences, 2022)
Objective: This study aimed to compare the effectiveness of mindfulness-based interventions (MBIs) and paradoxical intention therapy (PIT) on distress tolerance in adolescents with social anxiety symptoms. Methods and Materials: The study utilized a quasi-experimental design with pre-test, post-test, and two-month follow-up stages in three groups: MBI, PIT, and control. Sixty adolescents aged 12 to 18 with social anxiety symptoms were selected and randomly assigned to the groups. Distress tolerance was measured using the Distress Tolerance Scale (DTS) across all stages. Data were analyzed using repeated measures ANOVA to evaluate the impact of the interventions. Findings: The repeated measures ANOVA revealed significant within-group effects for distress tolerance across the three stages (F(1.58, 91.38) = 54.63, p < 0.001, η² = 0.49). The interaction effect between the intervention type and time was also significant (F(3.16, 182.48) = 20.76, p < 0.001, η² = 0.42). Post-hoc comparisons indicated that both the MBI and PIT groups showed significant improvements in distress tolerance from pre-test to post-test (p < 0.001) and from post-test to follow-up (p < 0.001), with no significant difference between the two intervention groups. Conclusion: The findings suggest that both mindfulness-based interventions and paradoxical intention therapy significantly enhance distress tolerance in adolescents with social anxiety symptoms, with effects persisting over time. These interventions should be considered in clinical practice for treating social anxiety in this population.